Dynamic Substructures, Volume 4 - Allen, Matthew; D’Ambrogio, Walter; Roettgen, Dan (River Publishers, 2023)
Dynamics of Coupled Structures, Volume 4: Proceedings of the 40th IMAC, A Conference and Exposition on Structural Dynamics, 2022, the fourth volume of nine from the Conference brings together contributions to this important area of research and engineering. The collection presents early findings and case studies on fundamental and applied aspects of the Dynamics of Coupled Structures, including papers on: Transfer Path Analysis Blocked Forces and Experimental Techniques Real-Time Hybrid Substructuring and Uncertainty Quantification in Substructuring Nonlinear Substructuring